Phylogeography of the White-Tailed Eagle Haliaeetus albicilla in Iceland using mitochondrial DNA - Sólveig Magnea Guðjónsdóttir 1995- (2020)
The white-tailed eagle (Haliaeetus albicilla) has a wide distribution along the Northern Hemisphere. During cold glacial periods it is believed to have found refugia south of its distribution range to wait out the cold and migrated back north to newly habitable areas after the end of last Ice age. The white-tailed eagle suffered persecution throughout its range in Europe and in many areas was close to extinction. These ecological occurrences shape the biodiversity and distribution of species. We analyzed 89 individuals in the north-western part of its range (Greenland, Iceland, Norway, Denmark and Estonia) for genetic structure and differentiation based on the whole mitochondrial genome. The aim was to get a better understanding of the white-tailed eagles phylogeography, especially in Iceland. We found a clear difference in mtDNA variation between countries, indicating separate populations. We also found evidence of admixture between the Icelandic and Greenlandic populations. Our results indicate that the Icelandic colonizers may have come from Norway on two occasions because the Icelandic population is divided into two haplogroups unrelated to geographical distribution. Both haplogroups showed distant connections to Norway but a strong, recent connection to Greenland.